Diagnosis Keperawatan pada Pasien Ventilator-Associated Pneumonia (VAP) di Unit Perawatan Intensif: Studi Retrospektif - Nur Hidayati; Dian Puspita Sari; Lilis Maghfuroh; Riyanto Faizin (Jurnal Kesehatan Terpadu, 2026)
Introduction: Pneumonia is an acute respiratory infection that often leads to respiratory failure and high mortality rates. It requires rapid and appropriate treatment to prevent fatal complications. Nurses play a crucial role in promptly identifying and treating pneumonia. A precise and accurate nursing diagnosis is essential for providing appropriate care. This study aims to identify signs, symptoms, and nursing diagnoses of pneumonia patients. Methods: This descriptive retrospective study used secondary medical record data. The study population consisted of 178 pneumonia patients admitted to the ICU at Lamongan Muhammadiyah Hospital from January to December 2024. These patients were selected using consecutive sampling, resulting in a sample size of 58. Data were collected from April 21 to May 19, 2025, using a recapitulation sheet, and were then analyzed descriptively. Results: The results showed that 67.2% of the patients experienced shortness of breath and cough. The most common nursing diagnosis for these patients is ineffective airway clearance (51.7%). Conclusion: Pneumonia consistently has a clinical impact and requires a structured nursing response. Future researchers are expected to conduct real-time research to collect sufficient data. Future researchers are expected to conduct real time research so that missing data can be identified at that time.